GRADE Equity Guidelines 4: Guidance on how to assess and address health equity within the evidence to decision process - Pottie, Kevin (J Clin Epidemiol, 2017)
OBJECTIVE: The aim of this paper is to provide detailed guidance on how to incorporate health equity within the GRADE (Grading Recommendations Assessment and Development Evidence) evidence to decision process. STUDY DESIGN AND SETTING: We developed this guidance based on the GRADE evidence to decision (EtD) framework, iteratively reviewing and modifying draft documents, in person discussion of project group members and input from other GRADE members. RESULTS: Considering the impact on health equity may be required, both in general guidelines, and guidelines that focus on disadvantaged populations. We suggest two approaches to incorporate equity considerations: 1) assessing the potential impact of interventions on equity and; 2) incorporating equity considerations when judging or weighing each of the evidence to decision criteria. We provide guidance and include illustrative examples. CONCLUSION: Guideline panels should consider the impact of recommendations on health equity with attention to remote and underserviced settings and disadvantaged populations. Guideline panels may wish to incorporate equity judgments across the evidence to decision framework. This is the fourth and final paper in a series about considering equity in the GRADE guideline development process. This series is coming from the GRADE equity subgroup.